Artesunate-amodiaquine versus artesunatesulfadoxine- pyrimethamine for uncomplicated falciparum malaria in children - Rampengan, Novie H.; Metusala, Jane; Chandra, Ronald; Salendu, Praevilia (Paediatrica Indonesiana, 2014)
Background Malaria is a major cause of morbidity and mortality in children, especially in developing countries. Art emisinin combination therapy (ACT) has higher rates of parasite clearance and inhibition of anti-malarial drugs resistance than non-ACT. Hence, we compared the efficacies of artesunate-amodiaquine (AS-AQ) versus artesunate-sulfadoxine pyrimethamine (AS-SP) combination therapies in children with uncomplicated falciparum malaria. Objective To compare the fever clearance time, parasite clearance time, and length of hospital stay in uncomplicated falciparum malaria patients treated with AS-AQ and AS-SP. Methods We reviewed the medical records of children aged 1- 14 years with uncomplicated falciparum malaria admitted to Prof. Dr. R. D. Kandou Hospital between January 2002 - June 2010. Treatment efficacy was evaluated by fever clearance time, parasite clearan ce time, and length of hospital stay. The differences of treatment efficacy between the two groups of therapy were an alyzed by independent T test. Results We identified 185 children with uncomplicated falciparum malaria, 104 cases were treated with AS-AQ while the other 81 received AS-SP. Parasite clearance time was shorter in AS-AQ group than in AS-SP group at 1.38 (SD 0.69) versus 1.91 (SD 0.93) days, respectively (95%CI of differences 0.3 0 to 0. 76, P<0.05) . The length of hospital stay was shorterin AS-AQ group than in the AS-SP group, at 5.01 (SD 1.22) versus 6.04 (SD 0.98) days, respectively (95%CI of differences 0. 71 to 1.35, P < 0.05). However, there was no statistically significant difference in fever clearance time between the groups. Conclusion AS-AQ combination therapy reduces parasite clearance time and length of hospital stay compared to AS-SP 46 • Paediatrlndones, Vol. 54, No. 1, January 2014 combination therapy in children with uncomplicated falciparum malaria.